The Effect of Pedal Peptide-Type Neuropeptide on Locomotor Behavior and Muscle Physiology in the Sea Cucumber Apostichopus japonicus - Ding, Kui; Zhang, Libin; Fan, Xinhao; Guo, Xueying; Liu, Xiang; Yang, Hongsheng (Frontiers in Physiology, 2020)
Neuropeptides are endogenous active substances that present in nervous tissues and participate in behavioral and physiological processes of the animal system. Locomotor behavior is basic to predation, escape, reproduction in animals, and neuropeptides play an important role in locomotion. In this study, the function of pedal peptide-type neuropeptide (PDP) in the process of locomotor behavior of the sea cucumber Apostichopus japonicus was evaluated. The locomotor behavior of A. japonicus was recorded by infrared camera before and after PDP administration, and muscle physiology was detected by ultra performance liquid chromatography and quadrupole time-off-light mass spectrometry (UPLC-Q-TOF-MS) to clarify the potential physiological mechanisms. The results showed that PDP enhanced the cumulative duration of moving significantly at 7th h after injection, and reduced the mean and maximum velocity by 16.90% and 14.22% in A. japonicus. The data of muscle metabolomics suggested that some significantly changed metabolites were related to locomotor behavior of sea cucumbers. The decreases of phosphatidylethanolamine (PE) and phosphatidylcholine (PC) might result in the increases of lysophosphatidylcholines (lysoPC) and lysophosphatidylethanolamine (lysoPE), and suggested the change of fluidity and permeability in the muscle cell membrane, which will affect the physiology and function of muscle cells, and finally alter the locomotor behavior. In addition, the increased level of arachidonic acid (ARA) might activate K+ ion channels and then affect the signaling of muscle cells, or promote the sensitivity of muscle cells to Ca2+ and then result in the contractility of longitudinal muscles in sea cucumbers. ARA was also involved in the linoleic acid metabolism which was the only pathway that disturbed significantly after PDP administration. In conclusion, PDP participated in the regulation of locomotor behavior in the sea cucumber, and the decreased PE and PC, increased lysoPC, lysoPE and ARA might be the potential physiological mechanisms that responsible for behavioral effects of PDP in A. japonicus.